(untitled) (Journal of Applied Learning and Teaching, 2020)
Technology is advancing, and with that, our students require digital empowerment and fluency to maximise their chances of success in their current and future personal and professional lives. In this paper, we build on the existing teacher leadership and digital literacy literatures. We theorise that authentic leader behaviours in higher education teachers offer a moderation effect on the relationship between teacher leadership and digital empowerment of students. We discuss the implications proposed from this critical review on increasing efficacy of student learning within the digital era. We see significance in this work, particularly as educators begin to test new digital pedagogies incorporating immersive learning environments, virtual reality, and augmented reality.